Comparison Of Two Different Alpha2 Agonists As Adjuvant In Balanced General Anaesthesia For Haemodynamic Stability & Olegamic Field In Transsphenoidal Pituitary Adenoma Removal In Tertiary Care Hospital (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: α2 agonists are first approved by FDA for only sedation in ICU. But at  present they are explored in various surgeries and in various routes. In present study we evaluate efficacy of Clonidine and Dexmedetomidine in neuro  anaesthesia for transsphenoidal removal of pituitary adenomas. AIMS & OBJECTIVES: To evaluate efficacy of Clonidine and Dexmedetomidine in neuro  anaesthesia for premedication, induction, haemodynamic stability, post operative smooth  extubation, recovery profile. STUDY DESIGN: Randomised double blind observation study. MATERIAL & METHODS: present study was done in V.S. general hospital & SVP  hospital, N.H.L. municipal medical college, Ahmedabad in neurosurgery & Anaesthesia  during 2015-2019. Adult 80 patients for elective surgery for pituitary adenoma  transsphenoidal Removal patients grade 1 or 2 enrolled in study and they are randomly  allocated to2 groups. Randomisation done by odd& even number in seal opaque envelope.  execution of randomisation at time of giving general anaesthesia. In group C: patients had received Inj. Clonidine pre operatively 1 mcg/kg loading dose over  10 min by infusion pump followed by 0.5 mcg/kg/hr after intubation. In group D: patients had received Inj. Dexmeditomidine pre operatively 1 mcg/kg loading  dose over 10 min by infusion pump followed by maintenance infusion 0.5 mcg/kg/hr after  intubation. Patients are induced with Propofol 2 mg/kg and Inj. Atracurium 0.5 mg/kg and intubated with  appropriate size endotracheal tube and maintained with O2, N2O, sevoflurane (0.2-0.5 MAC)  in close circuit and Inj. Vecuronium bromide on Drager Fabius GS Work Station. In both the  group infusion of drug was continued till dura closure by infusion pump. OBSERVATION & RESULTS: In both the groups patients had stable haemodynamics and smooth post operative recovery and extubation. Rate of reintubation was very less in both the  groups. CONCLUSION: α 2 agonists are good adjuvants for Transsphenoidal pituitary adenoma  removal. Dexmeditomidine is better than Clonidine in Transsphenoidal pituitary adenoma  removal.
Keywords: Dexmedetomidine; Clonidine; Transsphenoidal approach of pituitary adenoma; Olegamic field; Haemodynamic Stability